Job Satisfaction among Swedish Pharmacists - Sofia Mattsson; Maria Gustafsson (Pharmacy, 2020)
Understanding the role of pharmacists’ job satisfaction is important because a lack of job satisfaction might have negative impacts on patient care and safety. The aim of this cross-sectional study was to explore and compare job satisfaction among pharmacists graduating from the pharmacy programs at Umeå University, Sweden. Data concerning job satisfaction and associated factors were collected using an alumni survey conducted among pharmacists graduating between 2015 and 2018. Ethical committee approval is not required for this type of study in Sweden. A majority (92.6%) of the pharmacy graduates were female. A majority of the graduates (91.4%) were satisfied with their job most of the time or all of the time, which was similar to a previous investigation among pharmacists graduating between 2006 and 2014. High access to continuous professional development (CPD) was associated with higher job satisfaction (odds ratio (OR): 18.717 (95% confidence interval (CI): 1.685–207.871)). In total, 65.6% considered access to CPD to be high (i.e., satisfactory to very good). Variables like gender, age, employee category, workplace, years since graduation, and income did not affect job satisfaction. Knowledge regarding job satisfaction will enable employers to respond to employees’ needs, decrease turnover, and improve the work environment.